Accurate acoustic power measurement for low-intensity focused ultrasound using focal axial vibration velocity - Tao, Chenyang; Guo, Gepu; Ma, Qingyu; Tu, Juan; Zhang, Dong; Hu, Jimin (Journal of applied physics, 2017)
Low-intensity focused ultrasound is a form of therapy that can have reversible acoustothermal effects on biological tissue, depending on the exposure parameters. The acoustic power (AP) should be chosen with caution for the sake of safety. To recover the energy of counteracted radial vibrations at the focal point, an accurate AP measurement method using the focal axial vibration velocity (FAVV) is proposed in explicit formulae and is demonstrated experimentally using a laser vibrometer. The experimental APs for two transducers agree well with theoretical calculations and numerical simulations, showing that AP is proportional to the square of the FAVV, with a fixed power gain determined by the physical parameters of the transducers. The favorable results suggest that the FAVV can be used as a valuable parameter for non-contact AP measurement, providing a new strategy for accurate power control for low-intensity focused ultrasound in biomedical engineering.